Digitalization Strategy for MSME Development: Innovation, Partnership and Sustainable Solutions for Local Economy in Malang Regency - Kamil, Muhammad; Setyaningrum, Aisyah Firanti; Astutik, Juli (Journal Public Policy, 2024)
This study aims to discuss the government's strategy and collaboration in developing digital-based MSMEs to restore the regional economy. The fundamental problems of MSMEs in Malang Regency Government are declining sales (44%); capital (27%); distribution (12%); difficulty in raw materials (9%), and experiencing production problems (8%) decline in MSME sales turnover reaching (77.6%); asset decline reaching (42.7%) and workforce reduction reaching (46.1%). This study uses a qualitative research method with primary and secondary data collection. The data analysis uses Miles Huberman's theory to analyze data and draw conclusions. The results of this study indicate that the Malang government's strategy for restoring the community's economy is through a collaborative approach with the private sector and the community. The collaborative strategy is realized through digitalization with the "Pasti Bisa" application and virtual expo exhibitions to increase promotion and branding to increase business growth and improve the regional economy. Therefore, strategic partnerships and digital innovations encourage business growth and increase local revenue and stakeholder participation to improve transparency and accountability. Effective coordination between the government and private sector is often an obstacle to realizing a more robust and inclusive business ecosystem to enhance economic development.